The family under the bridge - Carlson, Natalie Savage; Williams, Garth (New York : Scholastic, 1958)
An old tramp, adopted by three fatherless children when their mother hides them under a bridge on the Seine, finds a home for mother and children and a job for himself.
R
680
R
Keywords: Tramps -- Fiction